An investigation into the need for counselling service at the Cape College of Education - Blom, Lana-Lorraine (Rhodes University, Faculty of Education, Department of Education, 1989)
Many students find that their greatest academic step is that from high school to college or university, and that it involves a transition affecting almost all aspects of their lives. In order to offer assistance to students experiencing transitional and other personal problems, Student Counselling Services have been established and are operature at most tertiary institutions in Southern Africa. Currently no such service exists on the campus of the Cape College of Education, Fort Beaufort. This exploratory study attempts to determine whether there is a need for such a service and further, to establish factors which might encourage or discourage students from using such a service. An open-ended questionnaire was administered to 178 students at the College in order to gain insight into their ideas and feelings and what they perceive their needs to be. Through an explication of the student protocols, several major themes emerged and are discussed in detail. The research findings suggest a need for the establishment of a counselling service, and shed some light on factors which need be considered should such a service be offered. The methodological approach is discussed as well as recommendations for improvements.
Keywords: Counseling in higher education; Teachers -- Training of -- South Africa -- Eastern Cape; Cape College of Education; Counseling